A Genome-Wide Integrative Association Study of DNA Methylation and Gene Expression Data and Later Life Cognitive Functioning in Monozygotic Twins - Soerensen, Mette; Hozakowska-Roszkowska, Dominika Marzena; Nygaard, Marianne; Larsen, Martin J.; Schwämmle, Veit; Christensen, Kaare; Christiansen, Lene; Tan, Qihua (Frontiers in Neuroscience, 2020)
Monozygotic twins are genetically identical but rarely phenotypically identical. Epigenetic and transcriptional variation could influence this phenotypic discordance. Investigation of intra-pair differences in molecular makers and a given phenotype in monozygotic twins controls most of the genetic contribution, enabling studies of the molecular features of the phenotype. This study aimed to identify genes associated with cognition in later life by integrated enrichment analyses of the results of intra-pair epigenome-wide and transcriptome-wide association analyses of cognition in 452 middle-aged and old-aged monozygotic twins (56-80 years). Integrated analyses were performed by an unsupervised approach using KeyPathwayMiner, and a supervised approach using the KEGG and Reactome databases. The unsupervised approach resulted in a 238 gene network, including the Alzheimer’s disease gene APP (Amyloid Beta Precursor Protein) and novel candidate genes. The supervised approach identified several enriched gene sets, including “neuroactive ligand receptor interaction”, “Neurotrophin signaling”, “Alzheimer’s disease” and “long-term depression”. In conclusion, this study identified several previously reported cognition genes and pathways and additionally puts forward novel candidates for further verification and validation.